2023
DOI: 10.23969/oikos.v7i1.6184
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Financial Distress, Leverage, Profitabilitas, Dan Pertumbuhan Perusahaan Terhadap Tax Avoidance Pada Perusahaan Sub Sektor Wholesale Yang Terdaftar Di Bei Tahun 2018-2020

Abstract: Salah satu sumber pendapatan negara diperoleh dari pajak. Pajak merupakan kontributor utama penerimaan negara. Terdapat beberapa faktor yang diduga dapat mempengaruhi praktik tax avoidance oleh perusahaan antara lain financial distress, leverage, profitabilitas, dan pertumbuhan perusahaan. Penelitian ini bertujuan untuk menganalisis pengaruh financial distress, leverage, profitabilitas, dan pertumbuhan perusahaan terhadap penghindaran pajak pada perusahaan subsektor wholesale yang terdaftar di Bursa Efek Indon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
0
0
Order By: Relevance
“…Then the value of the sales growth variable, which has a value of 0.1102, which if the other variables are considered constant, where sales growth when increases by 10 percent, it will add a tax avoidance value of 11.02 million rupiahs to 10 shares of Jakarta Islamic Index companies in the 2020-2022 period. The same results were also stated by several previous studies, including research conducted by, Marta and Nofryanti, (2023), Riyadi and Takarini, (2023), Theresia and Hariyanti, (2023), Irawati, Akbar, Wulandari, and Barli, (2020), Juliana, Arieftiara, and Nugraheni (2020), Sanjaya, (2022), Febriyanti, (2023 and Muthmainah and Hermanto, (2023), where the results of their research showed that the value of sales growth from each company has a positive influence on tax avoidance. That is, the higher the value of sales growth in a company will increase the company's tax avoidance practices.…”
Section: Panel Data Test Resultssupporting
confidence: 85%
“…Then the value of the sales growth variable, which has a value of 0.1102, which if the other variables are considered constant, where sales growth when increases by 10 percent, it will add a tax avoidance value of 11.02 million rupiahs to 10 shares of Jakarta Islamic Index companies in the 2020-2022 period. The same results were also stated by several previous studies, including research conducted by, Marta and Nofryanti, (2023), Riyadi and Takarini, (2023), Theresia and Hariyanti, (2023), Irawati, Akbar, Wulandari, and Barli, (2020), Juliana, Arieftiara, and Nugraheni (2020), Sanjaya, (2022), Febriyanti, (2023 and Muthmainah and Hermanto, (2023), where the results of their research showed that the value of sales growth from each company has a positive influence on tax avoidance. That is, the higher the value of sales growth in a company will increase the company's tax avoidance practices.…”
Section: Panel Data Test Resultssupporting
confidence: 85%
“…Pemisahan tersebut menimbulkan sebuah hubungan principal dengan agen yang disebut hubungan keagenan (Irwansyah dkk., 2020). Menurut teori keagenan, meskipun ada kalanya agen bertindak bertentangan dengan kepentingan principal, kepentingan kedua pihak pada akhirnya tetap selaras dari waktu ke waktu (Pratiwi & I M, 2020).…”
Section: Kajian Teori Teori Agensiunclassified